Sudden Sensorineural Hearing Loss: Clinical Characterization of Patients - Bhatta, Rishi; Shakya, Dipesh; KC, Arun (Nepalese Journal of ENT Head and Neck Surgery, 2014)
DOI: http://dx.doi.org/10.3126/njenthns.v3i2.10151 Nepalese Journal of Head and Neck Surgery Vol.3(2) 2012: 2-4